Speculative Investors and Transactions Tax: Evidence from the Housing Market - Fu, Yuming; Qian, Wenlan; Yeung, Bernard (Management Science, 2016)
This paper examines the impact of a policy change in transaction tax on speculators. The policy intervention took place in Singapore’s housing market; it effectively raised the transaction cost in a segment favored by short-term speculators. Relative to the unaffected control sample, we find that the rise in transaction cost, equivalent to a two- to three-percentage-point increase in transaction tax, reduced speculative trading in the treatment segment by 75% and raised its price volatility by 18%. It also significantly reduced price informativeness. We further show that the results are likely due to a relatively greater withdrawal by informed speculators than by destabilizing speculators following the transaction cost increase. This paper was accepted by Amit Seru, finance.